2020
DOI: 10.1016/j.artd.2020.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the femoral cement mantle in total hip arthroplasty using the direct anterior hip approach

Abstract: Background: Limited literature exists concerning the femoral cement mantle quality that can be achieved through an anterior approach in total hip arthroplasty (THA). We radiologically evaluated the quality and thickness of the femoral cement mantle in patients undergoing THA utilizing the direct anterior approach (DAA). Methods: Immediate postoperative anteroposterior and lateral radiographs of 116 consecutive patients who underwent hybrid or fully cemented THA using the DAA and cemented Quadra-C stem (Medacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A small study found the femoral cement mantle quality achieved through an anterior approach using the Barrack classification systems to be graded A in 39.25% (complete filling without radiolucent lines), B in 53.0% (a radiolucent line covering up to 50% of the cement-bone interface), and C in 7.75% (a radiolucent line covering between 50 and 99% of the cement-bone interface, or incomplete cement mantle) of anteroposterior radiographs and graded A in 40.1%, B in 51.75%, and C 9.5%, with 93% of stems in neutral alignment. 33 Another study found 92% of stems to be inserted in a neutral position with 85% achieving complete white out of cement in postoperative x-ray. 23 However, other studies have reported only 71% of stems to be inserted in neutral position using cemented fixation.…”
Section: Discussionmentioning
confidence: 99%
“…A small study found the femoral cement mantle quality achieved through an anterior approach using the Barrack classification systems to be graded A in 39.25% (complete filling without radiolucent lines), B in 53.0% (a radiolucent line covering up to 50% of the cement-bone interface), and C in 7.75% (a radiolucent line covering between 50 and 99% of the cement-bone interface, or incomplete cement mantle) of anteroposterior radiographs and graded A in 40.1%, B in 51.75%, and C 9.5%, with 93% of stems in neutral alignment. 33 Another study found 92% of stems to be inserted in a neutral position with 85% achieving complete white out of cement in postoperative x-ray. 23 However, other studies have reported only 71% of stems to be inserted in neutral position using cemented fixation.…”
Section: Discussionmentioning
confidence: 99%